Effects of Chemical Composition, Film Thickness, and Morphology on the Electrochromic Properties of Donor–Acceptor Conjugated Copolymers Based on Diketopyrrolopyrrole. Issue 8 (3rd July 2015) - Neo, Wei Teng; Shi, Zugui; Cho, Ching Mui; Chua, Soo‐Jin; Xu, Jianwei
Abstract: A series of diketopyrrolopyrrole (DPP) and propylenedioxythiophene (ProDOT)‐containing random copolymers with different donor‐to‐acceptor ratios is synthesized through Stille coupling polymerizations. The low‐bandgap polymers display dark tones with colors ranging from magenta to blue, and reveal reversible colored‐to‐transmissive electrochromism in absorption/transmission‐type devices with high optical contrasts (up to 48 and 77 % in the visible and near‐infrared regions, respectively), modest switching speeds (a few to tens of seconds) and coloration efficiencies (267–574 cm 2 C −1 ), as well as good long‐term ambient redox stabilities. The structure–performance relationship of the polymers, in particular, the role of donor‐to‐acceptor ratio, is investigated, and it is shown that an increase in the amount of acceptor in the polymers leads to slower oxidative but faster reductive switching, accompanied with enhancement of the redox stability. In addition, further study on the influence of film thickness and film morphology reveals that devices with higher optical contrasts are attainable from thicker polymer films at the expense of switching speeds; films with high uniformity and connectedness together with open, loose structures at submicron to micron scale are favorable for achieving good electrochromic performance. Abstract : On and off : A series of electrochromic diketopyrrolopyrrole‐based conjugated polymers are synthesized and characterized. Reversible colored‐to‐transmissive optical changes with high contrasts and ambient redox stabilities are observed (see figure). The influences of donor‐to‐acceptor ratio and film morphology on the electrochromic performance are addressed.